Incontinence training in children with cerebral palsy: A prospective controlled trial. Issue 4 (August 2022) - Samijn, Bieke; Van den Broeck, Christine; Plasschaert, Frank; Pascal, Aurelie; Deschepper, Ellen; Hoebeke, Piet; Van Laecke, Erik
Summary: Introduction: Urinary incontinence is the most frequently observed lower urinary tract symptom in children with cerebral palsy (CP). Being continent can positively influence quality of life of the child and the social environment. Objective: To investigate the effectiveness of incontinence training with urotherapy in children with CP. Study design: A population-based case-control study was conducted including 21 children with CP and 24 typically developing children between 5 and 12 years old, both with daytime incontinence or combined daytime incontinence and enuresis. Children received treatment for one year with three-monthly examination by means of uroflowmetry, a structured questionnaire and bladder diaries. Children started with three months of standard urotherapy. After three, six and nine months of training, specific urotherapy interventions (pelvic floor muscle training with biofeedback, alarm treatment or neuromodulation) and/or pharmacotherapy could be added to the initial treatment. Therapy was individualized to probable underlying conditions. Effectiveness was controlled for spontaneous improvement due to maturation and analysed by means of longitudinal linear models, generalized estimating equations and multilevel cumulative odds models. Comparison with typically developing children was assessed by means of Kaplan–Meier survival analysis. Results: Results suggest effectivity rate of incontinence training is lower and changes occur more slowly in time in children with CP compared to typically developing children (Figure). Within the group of children with CP, significant changes during one year of training were found for daytime incontinence (p < 0.001), frequency of daytime incontinence (p = 0.002), frequency of enuresis (p = 0.048), storage symptoms (p = 0.011), correct toilet posture (p = 0.034) and fecal incontinence (p = 0.026). Discussion: Maximum voided volume and fluid intake at the start of training were significantly lower in children with CP and could explain a delayed effectiveness of urotherapy. Treatment of constipation demonstrated a positive effect on maximum voided volume and should be initiated together with standard urotherapy when constipation is still present after implementation of a correct fluid intake schedule. Future research with a larger sample size is recommended. Conclusions: Incontinence training with urotherapy can be an effective treatment for urinary incontinence in children with cerebral palsy. In the current cohort, effectivity rate of incontinence training was lower and changes occurred more slowly in children with cerebral palsy compared to typically developing children. Summary Figure Percentage of patients with 50 % improvement daytime incontinence. Legend: –Children with cerebral palsy; ····Typically developing children; + Lost to follow-up. Summary Figure